(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Dietary services in the hospital are responsible for providing safe, clean, optimum nutrition in a scientific and sanitary way with minimum cost at right time and right place to right person. Impact of socio-demographic variations on quality dietary services process in tertiary care hospitals needs to be identified and appropriate recommendations for improvement. Objective: To evaluate the quality of dietary services in relation to socio-demographic variations in a tertiary hospital of Bangladesh. Methods: This study was cross sectional and descriptive in nature which included 101 purposively selected patients admitted at CMH Dhaka from July 2020 to December 2020. A face to face interview was taken using "Acute Care Hospital Foodservice Patient Satisfaction Questionnaire (ACHFPSQ)". Data were analyzed by SPSS v23 and appropriate statistical analyses were done. Results: More than half (61.4%) of the respondents were male and overall mean age (both male and female) were 56.02%. Majority (80.2%) of the respondents regarding food quality expressed their satisfaction as "good". Other facilities like physical environment (92.1%), food service satisfaction (83.2%) received a positive remarks. However low percentage of satisfaction observed in the above mentioned factors also. Mean scroing for food quality, meal service, staff issues and physical environment were 2.77, 4.83, 4.96 and 3.94 respectively. Association among sex and physical environment were found statistically significant (p=0.0). Conclusion: To improvise quality of dietary services, this study can effectively contribute in both public and private hospitals regarding their commitment to quality food service. Quality dietary services and patient satisfactions are directly connected to the healing of admitted people. JAFMC BangladesH, Vol 21, No 1 (June) 2025:28-31